The Urgency of the Confidentiality Principle in Restorative Justice Mechanisms - Kholilur Rahman; Arum Ayu Lestari; Markus Suryoutomo (Jurnal Suara Hukum, 2026)
One of the legal issues that is interesting and rarely receives attention in the application of restorative justice is the confidentiality principle. In international provisions, it is regulated in Paragraph 14 of the United Nations Basic Principles and in Paragraph 2 of the Council of Europe Recommendation. In several countries, such as the United States, Belgium, and others, it has attracted the attention of legal scholars. In contrast, research in Indonesia has yet to adequately address or explore this principle in detail. Accordingly, it is both relevant and necessary to investigate the significance of this principle within restorative justice mechanisms. The discussion begins with an exploration of the underlying legal rationale (ratio legis) behind the principle of Confidentiality in models of restorative justice, followed by an analysis of the urgency of reformulating restorative justice provisions within the Indonesian criminal justice system in a way that guarantees this principle. This study employed a normative legal research method, supported by several approaches, including the statute approach, comparative approach, and conceptual approach. The legal materials used consist of both primary and secondary legal sources. The main contribution of this research lies in its role as part of the law that ought to be (ius constituendum) for the reform of criminal procedure law in Indonesia.